Pendidikan dan Pengalaman Kerja Dewan Direksi di Negara Maju terhadap Pengungkapan Keberlanjutan - Umaroe, Indira Karima; Hamidah, Hamidah (E-Jurnal Akuntansi; Vol 33 No 3 (2023), 2023)
The board of directors as a strategic decision maker can influence corporate sustainability disclosures. The purpose of this study was to determine the effect of the education and work experience of directors in developed countries on sustainability disclosure. The research sample consisted of 64 companies listed on the IDX for the 2017-2021 period. Multiple linear regression in STATA software is used to analyze the data. The results of the analysis prove that the education and work experience of boards of directors in developed countries have a positive effect on corporate sustainability disclosures in Indonesia. The Board of Directors has integrated values regarding sustainability into itself. The novelty of this study is to differentiate the samples based on their disclosure, comprehensive or core options. This research provides practical implications for companies to pay attention to the background of directors in order to realize better sustainability disclosures. Keywords: Director’s Education; Director’s Working Experience; Sustainability Disclosures; Upper-Echelon Theory